Analisis Metode Perataan Penghasilan Dan Refinancing Dalam Manajemen Keuangan Perusahaan: Perspektif Teori Agensi Dan Prinsip Syariah - Gilang Ahdi Ramadhan; Syukri Iska; Azifah Hidayati (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the concepts, methods, driving factors, benefits, risks, and ethical implications of income smoothing and refinancing from the perspective of agency theory and sharia principles. The study used a descriptive qualitative method with a Systematic Literature Review (SLR) approach to 47 national and international journal articles published between 2001 and 2026. Data sources were obtained from the Scopus, Web of Science, Google Scholar, and DOAJ databases. The results show that income smoothing can increase the perception of company stability and reduce the cost of capital, but has the potential to reduce the quality of accounting information and create legal risks if carried out excessively and without transparency. Meanwhile, refinancing has been proven to improve financial structure and increase the efficiency of the cost of capital, although it can increase leverage if not managed carefully. From a sharia perspective, both strategies are permissible as long as they do not contain elements of usury, gharar, or fraud, and still uphold transparency and fairness. Therefore, their implementation needs to be supported by good corporate governance, effective risk management, and compliance with financial reporting standards.